Association between visceral adiposity index and prostate cancer in men aged 40 years and older: a nationwide cross-sectional study - Wentao Yao; Jiacheng Wu; Hongzhi Wang; Zongming Jia; Yinyi Zhou; Chendi Yang; Feng Xu; Ying Kong; Yuhua Huang (The Aging Male)
Objectives This study aimed to elucidate the correlation of Visceral Adiposity Index (VAI) with prostate cancer (PCa) among men aged 40 years and older in the United States.Methods Analysis included multivariate linear and logistic regression, smoothing curve fitting, and threshold effect evaluation using 2003-2010 National Health and Nutrition Examination Survey (NHANES) data. The stability of this relationship across demographic groups was assessed via subgroup analyses and interaction tests.Results Among 2,768 participants, those with elevated VAI displayed lower total prostate-specific antigen (tPSA) levels and reduced PCa risk. Each VAI unit elevation corresponded to a 0.075 ng/mL tPSA reduction [−0.075 (−0.145, −0.005)] and 18.8% PCa risk reduction [0.812 (0.687, 0.960)]. Top-quartile VAI individuals exhibited 0.282 ng/mL reduced tPSA [−0.282 (−0.557, −0.007)] and 49.7% reduced PCa risk [0.503 (0.282, 0.896)] relative to bottom-quartile counterparts. This inverse relationship was more pronounced in men ≥70 years. Moreover, VAI-tPSA in other races demonstrated a U-shaped pattern, with a 2.09 inflection point. At the same time, a Mexican American subgroup exhibited an inverted U-shape for VAI and PCa risk, with a 1.42 inflection point.Conclusion In men aged ≥70, VAI indicates an inverse PCa relationship. However, PSA-based PCa screening may be influenced in visceral-obese individuals aged <70.